Challenges to African Entrepreneurship in the 21st Century (Springer International Publishing, 2018)
This volume offers an overview of the critical challenges faced by aspiring African entrepreneurs and their coping strategies to sustain and develop their businesses. Contributors to this volume detail the constraints placed on African entrepreneurs through rich case studies and challenge African leaders and international donors to review their own behaviors if they hope for African entrepreneurs to succeed. Darko Opoku is Associate Professor of Africana Studies at Oberlin College, USA. Eve Sandberg is Professor in the Politics Department at Oberlin College, USA.